Okun's law and youth unemployment in Germany and Poland - Sophie Dunsch (International Journal of Management and Economics, 2016)
Unemployment rates, especially among youth, have increased in various countries of Europe over the last years. This paper examines changes in youth unemployment in Germany and Poland with Okun's law, testing that young employees are more vulnerable to the business cycle. I estimate country specific Okun coefficients for five different age cohorts. The results show that youth in Poland is more sensitive to business cycle fluctuations than adults, while in Germany the difference between the age cohorts is not that distinctive. In addition, cohort differences in Germany are not statistically significant, while they are significant in Poland but only with regard to the two oldest age cohorts. A further examination of the different labor market institutions affecting youth employment suggests long-term policy recommendations extending beyond GDP growth, such as structural reforms in education, as well as job-search assistance as short-term recommendation.
Keywords: E24; J64; 650; youth unemployment; Okun's Law; Poland; Germany